Summer School: Learning from a Teaching Practice from a Social Justice Perspective (Innovaciones Educativas, 2025)
The social outbreak that occurred in Chile in October 2019 interrupted the teaching in schools and, collaterally, the pedagogical practices of teachers in training. This motivated the implementation, in January 2020, of a summer school as an unconventional practice process in the initial teacher training programme of a public university in northern Chile, grouping all formative levels. The aims of this article are: a) to evaluate the process carried out during the design, implementation and evaluation of the summer school, and b) to analyse the pedagogical experience in terms of its contribution to an education in and for social justice of recognition and participatory equality. The methodology used was qualitative, taking into account the opinions of the teachers and students who participated in the summer school. The main findings show that the summer school favoured the construction of diverse learning linked to the pedagogical task and was constituted as a formative experience that promoted relationships based on affection, equal treatment, social esteem and collective participation. In conclusion, it is urgent to promote reflection on the practical processes in initial teacher training, as well as the protagonism of future teachers and the target community.
Keywords: Teacher Education; Pedagogical Practice; Social Justice; Public Education; Higher Education